Beam Dynamics Study on Intense Beam Linac LEBT - WANG Changqiang, YANG Jinghe, YANG Yu, YAN Jie, FAN Yuxuan, LYU Yuepeng, LI Liang, WANG Xiulong, WANG Guobao (Yuanzineng kexue jishu)
In the low energy beam transport line (LEBT), the increase in beam emittance caused by space charge, spherical aberration of Glaser lens and impurity particles in the beam will increase the difficulty of matching the beam with the subsequent structure. In addition, in order to meet the injection requirements of the experimental terminal and the annular accelerator, the beam needs to be cut into different time structures. The designed LEBT structure consists of dual Glaser, a beam chopper, double beam scraper, and other beam measuring elements. The dual Glaser were used to control the beam transverse parameters to meet the requirements of the RFQ accelerator and the beam chopper for beam emittance and Twiss parameters. The beam chopper is a longitudinal excision of the beam to achieve a different pulse time structure. Finally, the function of the double beam scraper is to control the beam emittance and scrape off the , impurity particles. Due to the influence of space charge force on the beam, the emittance of low energy intense particle beam increases with the increase of the length of the LEBT. In order to make the LEBT structure more compact, a Glaser lens with a pair of steering coils was developed to simultaneously achieve focusing and offset correction of the beam at the same position. According to the field distribution of the designed Glaser, the beam dynamics simulation software was used to calculate the beam matching from the ion source to the chopper and the RFQ accelerator. The beam chopper adopted the sloped bipole structure, calculated the beam deflection trajectory when the electric field between the poles exists, and optimized the plate structure so that the plate beam loss is zero when the plate high voltage is maximum. Under the same Glaser parameters, the beam envelopes of , and were calculated. According to the beam envelopes, a secondary scraper structure was designed between the dual Glasers and before the chopper to scrape off the impurity particles to avoid the influence of impurity particles on the beam transport and acceleration structure. According to the beam dynamics design, the beam experimental research was carried out. The experimental results show that the total beam intensity drawn from the ion source is 84 mA, and the beam intensity is 59.6 mA after collimation scraping in the LEBT outlet vacuum chamber, and the normalized RMS beam emittance is 0.245 mm·mrad using the Allison Scanner. At the same time, the beam chopping experiment was completed, and the longitudinal beam widths after cutting are 400 μs and 100 ns, respectively. The beam intensity and beam emittance can meet the expected requirements.